Administrative Burden in Bapenda Semarang City - Zahra, Kamelia; Aqhina Dzikrah Aurora (HM Publisher, 2024)
This research aims to examine the challenges and obstacles faced by the Regional Revenue Agency (Bapenda) of Semarang City in handling administrative burdens, as well as the efforts and steps taken to reduce and optimize these burdens. The research method used is a normative juridical approach with qualitative and inductive methods. Primary data were obtained through interviews with the Head of the Finance and Regional Property Subdivision of Bapenda Semarang, while secondary data consisted of relevant regulations. The results indicate that Bapenda Semarang faces high workloads, a large volume of administration, technological and information constraints, and a lack of public awareness regarding administrative obligations. Efforts made by Bapenda Semarang include the use of information systems, the implementation of tax reduction regulations, human resource development, and the expansion of service locations. Despite progress, there are still obstacles, such as the public's lack of understanding of information system features. Increasing the number of employees, implementing standard operating procedures (SOP), and providing incentives for staff involved are part of the applied solutions. This research provides a comprehensive overview of the challenges and efforts made by Bapenda Semarang in handling administrative burdens. Suggestions involve increasing public awareness, optimizing information systems, improving technological infrastructure, and developing human resources.